Sejarah Perkembangan Bimbingan Konseling (BK) - Hidayani Syam; Amelia Maharani; Rafita Gusti Putri; Agus Salim (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Guidance & counseling (BK) is a field of science that is serious about helping individuals with self-development, problem-solving, & decision-making.Its development has taken place from the antique era to the formal discipline known today.In antique Greece, figures such as Socrates & Plato emphasized the importance of conversation & reflection on self-development.Later, in medieval times, the concept of guidance existed through the work of religion, especially in putting moral direction.The most recent era was marked by the emergence of career guidance in the United States in the early 20th century, pioneered by Frank Parsons, known as the "Father of Career Guidance". He founded the Boston Vocational Bureau in 1908 to help individuals determine occupations that are in sync with their talents & interests.This development accelerated after World War II, when the need for psychological & social support increased.In Indonesia, guidance & counseling became known in the 1960s, along with the impact of the latest education & Western psychology.BK was integrated into the formal education system to help students in academic, personal, social, & career aspects. o date, counseling continues to evolve by adopting new approaches, such as technology-based counseling and multicultural approaches, to respond to the increasingly complex needs of the people.The history of counseling reflects a transformation based on simple methods towards a structured scientific approach, using the primary goal of helping individuals reach their full potential.